Analisis Penerapan Tiket Elektronik KRL Jabodetabek - Kuswati, Atik S; Herawati, Herawati (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
T7re goal of electronic ticketing in commuter train Jabodetahek is to improving passenger services andoperator fermofmance. Nowdatjs, there are three level of KRL senrices such as Express AC, ACEconomic, and economic class so that it is difficu.lt to implement that program.T7te studt; will analyze tlte program of electronic ticketing implementation from operator and passengerside. Factor analyze is used to identifiJ the factors which influence electronic ticket implementation.T7te analysis result is grouped into utilihj, eficienetj, recharge, pm1ment medumism, sosialization andsafeh;.Implementation of electronic ticketing SIJStem need some requirements such as ticket design in accorda.nce with the tariff SIJStem, supporting both the Juzrdware components and software whidi Juzrdwareconsist of tickets, ticket machines and software, experimental phase, supennsion and maintenance.In addition, the people's respon or readiness of communihJ should be considered towardsimplementing electronic ticketing.Keyword: Electronic tikecting, Services, Cornrnutter train Jabodetabek.